2016
DOI: 10.1186/s13071-016-1768-y
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modelling of lymphatic filariasis elimination programmes in India: required duration of mass drug administration and post-treatment level of infection indicators

Abstract: BackgroundIndia has made great progress towards the elimination of lymphatic filariasis. By 2015, most endemic districts had completed at least five annual rounds of mass drug administration (MDA). The next challenge is to determine when MDA can be stopped. We performed a simulation study with the individual-based model LYMFASIM to help clarify this.MethodsWe used a model-variant for Indian settings. We considered different hypotheses on detectability of antigenaemia (Ag) in relation to underlying adult worm b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 77 publications
1
51
0
1
Order By: Relevance
“…2,6,7 However, studies have shown that in areas with high mf prevalence, more than six rounds of MDA were required to achieve interruption with low epidemiological coverage. 10,19 Other factors that may be responsible for the delay in mf interruption of transmission in high prevalent areas include poor compliance. 8 In this study, there seemed to be no differences in the reported MDA epidemiological coverage.…”
Section: Discussionmentioning
confidence: 99%
“…2,6,7 However, studies have shown that in areas with high mf prevalence, more than six rounds of MDA were required to achieve interruption with low epidemiological coverage. 10,19 Other factors that may be responsible for the delay in mf interruption of transmission in high prevalent areas include poor compliance. 8 In this study, there seemed to be no differences in the reported MDA epidemiological coverage.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with drugs alone is not effective as a prophylaxis against LF. There is a need for a more sustained approach such as a prophylactic vaccination to stop transmission and eliminate LF from the endemic areas (Dakshinamoorthy et al 2013c; Jambulingam et al 2016; Harris et al 2017). Our laboratory and others have identified several potential vaccine antigens that are shown to confer significant protection against challenge infections in experimental animals (Samykutty et al 2010; Dakshinamoorthy et al 2013b, Dakshinamoorthy et al 2013c; Arumugam et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Assuming these are applicable to our study area it may be seen that though both hotspots and non‐spots recorded same levels of compliance at 55%, a higher proportion of Ag (Mf) positive individuals and positive households were found in hotspots. These observations imply that the dynamics of impact of the MDA in an area may not only be influenced by the baseline endemicity but also by current mosquitogenic conditions prevailing in that area. Therefore, for interrupting transmission wherever appropriate, MDA may be supplemented with localised vector control measures, as indicated by the simulation models: annual MDA with vector control measures will be a better performing strategy in bringing down both human and vector infection well below the recommended thresholds for LF elimination.…”
Section: Discussionmentioning
confidence: 97%